2012
DOI: 10.1063/1.4772497
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of photoelectrochemical-oxidized p-GaSb films

Abstract: GaSb oxide films were directly formed on the p-GaSb films using the bias-assisted photoelectrochemical (PEC) oxidation method. X-ray photoelectron spectroscopy analysis indicated that the resulting GaSb oxide films consisted of Ga2O3, Sb2O3, and Sb2O5. Different from the non-PEC oxides, the PEC derived oxide contained much more Sb2O5 than Sb2O3. Besides, the interface state density between the PEC oxide and p-GaSb was lower than that of the ordinary oxide/p-GaSb interface. The high quality of the PEC-oxidized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Table listed the short circuit current density ( J sc ), open circuit voltage ( V oc ), fill factor ( FF ), and conversion efficient ( η ) of these solar cells A, B, and C. It was found that the short circuit current density of 57.09 mA/cm 2 for solar cell B was larger than that of 50.82 mA/cm 2 for solar cell C. More surface recombination centers were induced on the as‐etched surface of solar cell C, because the etching process for removing the p + ‐GaSb layer caused damage to the p ‐GaSb surface. To reduce the induced surface recombination centers, the bias‐assisted PEC oxidation process was performed to form a PEC oxide layer on the p ‐GaSb surface as an oxide passivation layer after the etching process in solar cell B. Consequently, the interface state density between the PEC oxide passivation layer and the p ‐GaSb was reduced to decrease the carrier recombination on the surface of solar cell B. Therefore, the improvement in short circuit current density was attributed to that the surface carrier recombination in solar cell B was suppressed by the bias‐assisted PEC passivation function.…”
Section: Experimental Process and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table listed the short circuit current density ( J sc ), open circuit voltage ( V oc ), fill factor ( FF ), and conversion efficient ( η ) of these solar cells A, B, and C. It was found that the short circuit current density of 57.09 mA/cm 2 for solar cell B was larger than that of 50.82 mA/cm 2 for solar cell C. More surface recombination centers were induced on the as‐etched surface of solar cell C, because the etching process for removing the p + ‐GaSb layer caused damage to the p ‐GaSb surface. To reduce the induced surface recombination centers, the bias‐assisted PEC oxidation process was performed to form a PEC oxide layer on the p ‐GaSb surface as an oxide passivation layer after the etching process in solar cell B. Consequently, the interface state density between the PEC oxide passivation layer and the p ‐GaSb was reduced to decrease the carrier recombination on the surface of solar cell B. Therefore, the improvement in short circuit current density was attributed to that the surface carrier recombination in solar cell B was suppressed by the bias‐assisted PEC passivation function.…”
Section: Experimental Process and Resultsmentioning
confidence: 99%
“…During the PEC growth process, the laser beam intensity and the bias voltage were kept to be 6.5 mW/cm 2 and 4 V, respectively, and the pH value of the electrolytic solution was set around 12.5. The working mechanism of the bias‐assisted PEC oxidation method was reported, previously . To reduce the light reflection from the surface of the solar cells, an ITO nanorod array was grown on the p ‐GaSb surface using an oblique‐angle electron‐beam deposition system with an optimized oblique‐angle of 30°.…”
Section: Experimental Process and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the important III/V compound semiconductor material, gallium antimonide (GaSb) has attracted considerable attention as potential building blocks for a variety of optical and electronic components, such as infrared imaging device, thermoelectric sensor, and high-speed electronics, especially photodetectors [11][12][13][14]. Although GaSbbased photodetectors usually exhibited photoconduction features, till now, most of the GaSb-based photodetectors are built on either bulk materials, thin films or nanostructured superlattice.…”
Section: Introductionmentioning
confidence: 99%